Blood on Page, Blood on Stage: a Look Into Artistic Creativity and Transfiguration Through Vampires in Liz Lochhead's Blood and Ice and Dracula - AKYAR, AYLİN (İstanbul Kültür Üniversitesi, 2025)
Blood and Ice (1985, 2009) and Dracula (1988) are listed as Scottish playwright Liz Lochhead's sui generis contributions to Feminist Gothic drama. Drawing on the framework of feminist literary theory, specifically Adrienne Rich's concept of "re-vision," this study analyses how Lochhead reimagines canonical Romantic/Gothic figures, respectively Mary Shelley and Count Dracula through a feminist lens. However, their arising from Gothic genre is not the only connection between these two plays. This thesis puts forward that on the one hand, in Lochhead's Blood and Ice the metaphorical vampire, Lord Byron as John William Polidori's primary source for The Vampyre (1819), assumes the role of Mary's mirror / double in her quest for artistic creativity, compelling her literary authorship and revealing the contradictions embedded in her creation of Frankenstein (1818, 1831). Mary Shelley's Frankenstein can be regarded as a monstrous autobiography par excellence, since this Gothic tale carries the burden of her self-divisions, which transfigure her artistic creation as well. On the other hand, Bram Stoker's Count Dracula in his Gothic fin de siècle novel Dracula (1897) is the fictional vampire — the epitome of transgressive desire and sexuality in disguise. In Lochhead's feminist re-vision in Dracula, Bram Stoker's Vampire is portrayed as a liberating and empowering force of nature aligned with women, a trigger for transformation for the women who sought to free themselves from the societal constraints. In both texts, Liz Lochhead turns the tables with her revisionist stance. Lochhead's plays within the scope of this thesis' discussion ultimately depict the Gothic/Romantic 'Vampire' as a transfiguring figure, disrupting the boundaries between Self/Other, along with sexuality and gender.
Keywords: Feminist Re-Vision; Feminist Re-Writing; Adaptation; Feminist Drama; Gothic Drama; Artistic Creativity; Authorship; Gender; Queer Vampires; Mary Shelley; Female Vampires; Dracula